Correlation Analysis of Broiler Production Traits, A Case Study in Humid Tropical East Kalimantan - Amani Aldiyanti; Dani Nur Arifin; Anhar Faisal Fanani; Andi Nurmasytha; Akhmat Rizkuna (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2025)
Broiler production in humid tropical regions such as East Kalimantan faces challenges from persistently high temperature and humidity, which can affect feed intake, growth rate, and feed conversion efficiency. This study aimed to examine the correlation among key production parameters feed intake, daily weight gain, feed conversion ratio (FCR), and mortality across commercial broiler farms with different housing systems in East Kalimantan. An observational field study was conducted on four broiler farms rearing Ross, Lohmann, and Cobb strains under both closed-house and open-house environments. Data were analyzed using Pearson correlation after normality testing. The average feed intake was 3.70 ± 0.64 kg/bird, final body weight 2.08 ± 0.13 kg, total body weight gain 2.04 ± 0.13 kg, FCR 1.81 ± 0.23, and mortality 3.92 ± 0.74. A significant positive correlation was found between feed intake and FCR (r = 0.961; p < 0.05), and a very strong correlation between body weight gain and final body weight (r = 1.000; p < 0.01). Broilers raised in closed-house systems showed lower FCR and more stable growth compared to those in open-house systems. These findings highlight the crucial role of microclimatic control in improving feed efficiency and growth performance of broilers in humid tropical environments. Optimizing housing design and environmental management is therefore recommended to enhance productivity and economic efficiency of broiler farming in tropical regions.